Uganda rising - Lawton, Alison; Miller, Jesse James; McCormack, Pete, 1965-; McCormack, Pete, 1965-; Spacey, Kevin (Mindset Media, 2006)
For the past 20 years, the Acholi people of northern Uganda have been kidnapped, held hostage, terrorized and killed by one of their own, Joseph Kony. As the leader and self-styled 'prophet' of the Lord's Resistance Army (LRA), Kony has been engaged in an undeclared civil war against Yoweri Museveni's government. As part of this war, over 25,000 children have been abducted, trained under particularly brutal regimes, and sent out into the field as soldiers. Museveni has attempted to check the LRA by detaining the women and children of northern Uganda in sprawling internal displacement camps. A brief history of the history of Uganda prefaces the exploration of the havoc Kony has wreaked on this otherwise progressive, stable African nation.